2023
DOI: 10.1007/s00018-023-04832-6
|View full text |Cite
|
Sign up to set email alerts
|

Ageing in the brain: mechanisms and rejuvenating strategies

Abstract: Ageing is characterized by the progressive loss of cellular homeostasis, leading to an overall decline of the organism’s fitness. In the brain, ageing is highly associated with cognitive decline and neurodegenerative diseases. With the rise in life expectancy, characterizing the brain ageing process becomes fundamental for developing therapeutic interventions against the increased incidence of age-related neurodegenerative diseases and to aim for an increase in human life span and, more importantly, health spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 240 publications
(291 reference statements)
0
3
0
Order By: Relevance
“…The aging process is marked by chronic, low-grade systemic inflammation in the absence of overt infection, constituting a significant risk factor for morbidity and mortality [37]. Brain aging is defined by cognitive decline and memory deficits, where the major mechanisms involved are oxidative stress and neuroinflammation [38]. Phospholipids in the brain are sensitive to ROS-induced damage [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aging process is marked by chronic, low-grade systemic inflammation in the absence of overt infection, constituting a significant risk factor for morbidity and mortality [37]. Brain aging is defined by cognitive decline and memory deficits, where the major mechanisms involved are oxidative stress and neuroinflammation [38]. Phospholipids in the brain are sensitive to ROS-induced damage [39].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the involvement of BDNF/p-ERK/p-CREB signaling occurs during the cognition-enhancing effects of EA-L3, generating new brain cells and strengthening existing ones to avert the consequences of aging. It has also been demonstrated that BDNF can interact with oxygen radicals (ROS), an imbalance associated with aging processes [38]. On the other hand, BDNF also increases CREB phosphorylation and its nuclear localization by reducing the binding of NF-κB and CBP, which further inhibits the production of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation-competent glial cells can undergo senescence both in vitro and in vivo , and contribute to neuroinflammation in the aging brain. Astrocytes can become reactive or senescent with aging, depending on stressful stimuli, contributing to the loss of cognitive function through inflammatory mediators ( Cohen and Torres, 2019 ; Escartin et al, 2021 ; Lopez-Teros et al, 2022 ; Gaspar-Silva et al, 2023 ). Astrocyte senescence implies permanent cell cycle arrest, increased cell size, and several characteristics that involve a secretory profile called senescent associated secretory phenotype (SAPS) ( Rodier and Campisi, 2011 ), the presence of DNA damage or “scars,” changes in heterochromatin called Senescence-Associated Heterochromatin Foci (SAHF) ( Narita et al, 2003 ), increment of b-galactosidase enzyme activity ( Dimri et al, 1995 ), lipofuscin accumulation, and a decrease in lamin B1 ( Shimi et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%